Incidence and Risk of PD-1/PD-L1 Inhibitor-associated Pneumonia in Advance Cancer Patients: A Meta-analysis - Kang CHEN; Butong SUN (Chinese Journal of Lung Cancer, 2020)
Background and objective Immune checkpoint inhibitors (ICIs) have good efficacy on most advanced tumors, which brings new hope to patients with advanced tumors. However, the immune system activated by ICIs may attack human normal tissues and organs, resulting in corresponding immunotoxicity, such as checkpoint inhibitor pneumonitis. This article carried out a meta-analysis on the incidence and risk of programmed cell death protein 1 (PD-1) and programmed cell death protein ligand 1 (PD-L1) inhibitor-associated pneumonia in advanced tumors patients. Methods The computer retrieval of PubMed, Cochrane Library, EMbase and CNKI was performed, and the studies on the occurrence rate of PD-1/PD-L1 inhibitor-associated pneumonia in terminal cancer patients were collected, with the retrieval time limit of January 2000 to January 2020. Statistical analysis was conducted by using Revman 5.3 and R 3.6.2 software to compare the occurrence rate of pneumonia under different circumstances. Results 15 studies were included, involving 8,642 patients, of which those with PD-1/PD-L1 inhibitor were treatment group, and those with chemotherapy were control group. The odds radio of all grades of immune pneumonia was 6.63, and that of high grade was 4.87. The occurrence rate of all grades of pneumonia in the ICI group with non-small cell lung cancer (NSCLC) was 1.658 times than other tumors, and that of high grade was 2.299 times. The occurrence rate of all grades of pneumonia in second-line or more treatment with ICI was 0.489 times than that in first-line, and that of high grade was 0.449 times than that in first-line or more treatment with ICI. Conclusion Compared with chemotherapy, the risk of immune-associated pneumonia is higher in PD-1 and PD-L1 inhibitors, and its occurrence risk is high in the ICI group with NSCLC and the first-line treatment with ICI. This paper provides guidance for clinic treatment of terminal cancers and prevention of complications.